Relationship between gene polymorphisms of pulmonary alveolar surfactant protein D and genetic susceptibility in elderly Han patients with chronic obstructive pulmonary disease in Sichuan - Shi Fangyu; Huang Chen; Wu Ruiyan; Huang Yan (Guoji laonian yixue zazhi)
[Objective] To explore the relationship between gene polymorphisms of pulmonary alveolar surfactant protein (SP)-D and genetic susceptibility in elderly Han patients with chronic obstructive pulmonary disease (COPD) in Sichuan. [Methods] A total of 125 elderly patients with COPD and 125 healthy controls with similar general data (age, gender, body mass index) at West China Hospital of Sichuan University were enrolled as the COPD group and control group between October 2020 and March 2023, respectively. The blood samples were collected to obtain SP-D gene polymorphisms (frequencies of alleles and genotypes at rs721917 and rs2245121 loci) by PCR restriction fragment length polymorphism. [Results] There was no significant difference in gender, age or body mass index between the COPD group and the control group (P>0.05). The proportion of smoking history and smoking frequency in the COPD group were higher than those in the control group, while the one-second rate was lower than that in the control group (P<0.05). There were significant differences in frequencies of genotypes (G/G, G/A, A/A) at the rs721917G/A locus between the COPD group and the control group (29.6%, 56.0%, 14.4% vs 43.2%, 40.8%, 16.0%; P<0.05), but there was no significant difference in frequencies of alleles (G, A) at rs721917G/A locus between the two groups (57.6%, 42.4% vs 63.6%, 36.4%; P>0.05). There was no significant difference in frequencies of genotypes (G/G, G/A, A/A) at rs2245121G/A locus between the COPD group and the control group (60.8%, 36.0%, 3.2% vs 60.0%, 37.6%, 2.4%; P>0.05), and there was also no significant difference in frequencies of alleles (G, A) at rs2245121 locus between the two groups (78.8%, 21.2% vs 78.8%, 21.2%; P>0.05). [Conclusion] The polymorphisms of the SP-D gene at rs721917 locus may be correlated with genetic susceptibility in elderly Han patients with COPD in Sichuan, G/A genotype may be a susceptible genotype, and polymorphisms of the SP-D gene at rs2245121 locus are not correlated with the genetic susceptibility.